QTL Mapping for Agronomic and Adaptive Traits Confirmed Pleiotropic Effect of mog Gene in Black Gram [Vigna mungo (L.) Hepper] - Somta, Prakit; Chen, Jingbin; Yimram, Tarika; Yundaeng, Chutintorn; Yuan, Xingxing; Tomooka, Norihiko; Chen, Xin (Frontiers in Genetics, 2020)
Organ size and architecture of plants are important traits affecting crop yield and agronomic practices. An induced mutant, multiple-organ gigantism (MOG), of black gram (Vigna mungo) has been obtained, which shows gigantic leaves, fruit, seed, and architecture (plant height) but lower number of pods per plant. These traits are a pleiotropic effect of a single recessive gene, mog. In this study, we investigated variation of 16 agronomic and adaptive traits in a recombinant inbred line (RIL) population derived from a cross between the MOG mutant (V. mungo var. mungo) and wild black gram (V. mungo var. silvestris) accession TC2210 and identified quantitative trait loci (QTLs) controlling those traits to gain a better understanding of the effect of the mog gene on breeding. The results showed that most of the traits (100-seed weight, leaf size, and plant height) showed moderate narrow-sense heritability (h2) (45–65%), while pod size and seed length (SDL) showed high h2 (>75%) and pod dehiscence (shattering), and seed width (SDW) and days to flowering showed low h2 (<35%). The QTLs for the traits were mapped onto a high-density linkage map developed for the RIL population. Inclusive composite interval mapping identified 42 QTLs in total for the 16 traits with number of QTLs per trait ranging from one to six. Major QTLs for the MOG phenotypes were clustered on linkage group (LG) 6, confirming the pleiotropic effect of the mog gene. Effect of the mog gene/QTL for the MOG phenotypic variations was not high, ranging from about 15% in plant height to 40% in leaf size. For 100-seed weight, which is the most interesting trait, the mog gene/QTL contributed about 30% of the total trait variation and showed an additive effect of only 0.51 g, which is only about 1.5-fold higher than that of the other five QTLs detected for this trait. These results indicated that mog gene expression is highly affected by environment and the effect of the gene toward organ size and plant height is not extraordinarily high. Implications of the findings of this study and exploiting of the MOG mutant in breeding were also discussed.